2017
DOI: 10.1080/10942912.2017.1373663
|View full text |Cite
|
Sign up to set email alerts
|

Shelf life improvement of grape (Vitis viniferaL. cv. Rish Baba) using nitric oxide (NO) during chilling damage

Abstract: View related articlesView Crossmark data Citing articles: 4 View citing articlesShelf life improvement of grape (Vitis vinifera L. cv. Rish Baba) using nitric oxide (NO) during chilling damage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The increased activity of antioxidant enzymes obtained by this research is in agreement with Ghorbani et al [ 50 ], who showed that nitric oxide reduced decay on grape cv. Rish Baba and increased POD, APX and SOD activity, and this effect was correlated with enhanced antioxidant enzyme activities.…”
Section: Discussionsupporting
confidence: 93%
“…The increased activity of antioxidant enzymes obtained by this research is in agreement with Ghorbani et al [ 50 ], who showed that nitric oxide reduced decay on grape cv. Rish Baba and increased POD, APX and SOD activity, and this effect was correlated with enhanced antioxidant enzyme activities.…”
Section: Discussionsupporting
confidence: 93%
“…MDA content is an indication of membrane lipid peroxidation [ 51 ]. MDA content and cell membrane permeability can be used to reflect the membrane integrity of cells and the degree of membrane injury [ 52 ]. Our study indicated that exogenous MT treatment significantly inhibited MDA accumulation and decreased cell membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The storage life of guavas can be prolonged by postharvest immersion treatment with SNP [ 34 ]. NO has a beneficial effect on the delay of postharvest grapefruit senescence [ 35 ]. NO treatment also significantly improved the shelf life of harvested pointed gourds [ 36 ].…”
Section: Effects Of No In Postharvest Fruitsmentioning
confidence: 99%
“…Guava fruits under NO treatment exhibited the minimum loss of chlorophyll, SSC and acidity, and a slower increase in carotenoid pigments [ 34 ] ( Table 1 ). NO could increase the contents of vitamin C, organic acids and total soluble solids (SSs) in grapefruits during cold storage, suggesting that NO may have potential applications in postharvest treatments to maintain fruit quality [ 35 ]. NO application effectively maintained chlorophyll and suppressed the yellow colour development undergone by pointed gourds [ 36 ].…”
Section: Effects Of No In Postharvest Fruitsmentioning
confidence: 99%
See 1 more Smart Citation